Long term performance of gravel base course layers in asphalt pavements. (December 2018) - Titi, Hani H.; Dakwar, Mahmoud; Sooman, Mohammad; Tabatabai, Habib
Abstract: This research investigated the performance of base layer aggregates in HMA pavements using laboratory tests (standard compaction, particle size analysis, Atterberg Limits, sodium sulfate soundness, Micro-Deval abrasion, absorption, specific gravity, and soaked CBR) on existing base layer materials as well as pavement surface visual and automated distress surveys. The purpose of this research was to investigate potential degradation of aggregate bases, strength variations over time, and the likely causes for both. Analysis of laboratory and field test results indicated significant variability in the properties and characteristics of base layer aggregate materials in various pavement test sections. Based on the results of the laboratory and field tests, the research team believes that the long-term performance of the base layer aggregates impacted the overall pavement performance of the corresponding test sections. While base aggregate materials in general did not exhibit severe degradation or disintegration – as demonstrated by laboratory tests – nor significant contamination from subgrade, the performance of such materials was lower compared with typical crushed stone materials.